Role of inositol 1,4,5-trisphosphate receptor type 1 in ATP-induced nuclear Ca2+ signal and hypertrophy in atrial myocytes - Kim, Joon-Chul; Son, Min-Jeong; Le, Qui Anh; Woo, Sun-Hee (Biochemical and biophysical research communications, 2018)
Inositol 1,4,5-trisphosphate receptor type 1 (IP3R1) is expressed in atrial muscle, but not in ventricle, and they are abundant in the perinucleus. We investigated the role of IP3R1 in the regulations of local Ca2+ signal and cell size in HL-1 atrial myocytes under stimulation by IP3-generating chemical messenger, ATP. Assessment of nuclear and cytosolic Ca2+ signal using confocal Ca2+ imaging revealed that IP3 generation by ATP (1 mM) induced monophasic nuclear Ca2+ increase, followed by cytosolic Ca2+ oscillation. Genetic knock-down (KD) of IP3R1 eliminated the monophasic nuclear Ca2+ signal and slowed the cytosolic Ca2+ oscillation upon ATP exposure. Prolonged application of ATP as well as other known hypertrophic agonists (endothelin-1 and phenylephrine) increased cell size in wild-type cells, but not in IP3R1 KD cells. Our data indicate that IP3R1 mediates sustained elevation in nuclear Ca2+ level and facilitates cytosolic Ca2+ oscillation upon external ATP increase, and further suggests possible role of nuclear IP3R1 in atrial hypertrophy. •IP3 receptor type 1 (IP3R1) are expressed in atrial cell perinucleus.•IP3R1 mediates ATP-induced sustained nuclear Ca2+ increase in HL-1 atrial cells.•IP3R1 contributes to higher sensitivity of nuclear release sites upon IP3 increase.•Larger Ca2+ content in perinuclear store of atrial cells involves IP3R1.•IP3R1 signaling may play a role in ATP-induced atrial cell hypertrophy.